Preparation and properties of irradiation crosslinked chlorinated polyethylene composites reinforced with carbon black or silica - LI Ya-ru, ZHANG Zhen-xiu (Hecheng xiangjiao gongye)
With chlorinated polyethylene as matrix and silica or carbon black as reinforcement fillers, chlorinated polyethylene composites were prepared by crosslinking under high-energy electron beam irradiation. The effects of filler amount and irradiation dose on the properties of the composites were investigated. The results showed that the Mooney viscosity of the composites increased significantly with the increase of filler amount, forming a filler network structure and exhibiting an obvious Payne effect. When the filler amount was the same, the tensile strength and tear strength of the composites increased with the increase of irradiation dose. Under the same irradiation dose, the tensile strength of composites increased first and then decreased when the filler amount increased. When the irradiation dose was 40 kGy and filler amount was 40 phr (by mass), the tensile strength of the chlorinated polyethylene/silica composite was 14.31 MPa, tear strength was 40.6 N/mm and elongation at break was 575%. The tensile strength of the chlorinated polyethylene/carbon black composite was 16.21 MPa, the tear strength was 47.3 N/mm, and the elongation at break was 579%.